CFD prediction of dust pollution and impact on an isolated ground-mounted solar photovoltaic system. (February 2019) - Lu, Hao; Zhao, Wenjun
Abstract: This paper numerically studied dust deposition behaviors and their influences on an isolated ground-mounted solar PV system. The shear stress transport k-ω turbulence model with user-defined function inlet profiles was established to predict turbulent air flow around solar PV system. Moreover, discrete particle model was employed to predict dust deposition rates on PV panel. After grid independent study and numerical validation with related experimental data, turbulent wind flow fields around solar PV system, dust deposition rates on PV panel with different dust diameters and wind velocities as well as their influences on the output efficiency for different types of PV modules were predicted and analyzed carefully. The results showed that dust deposition rate on PV panel first increases and then decreases when dust diameter increases. However, the dust deposition profiles are similar for different wind velocities. The highest deposition rate is 13.71% for 100 μm particles when U Hp = 1.3 m/s ( U Hp is wind velocity at solar PV panel height) while is 14.28% for 150 μm particles when U Hp = 2.6 m/s. The effects of interception, gravitation and mass inertia are the main mechanisms for dust deposition. Furthermore, dust deposition effect on PV output efficiency was predicted by a simplified model based on present computational fluid dynamics simulation and experimental measurement. Highlights: Effects of dust deposition on a ground-mounted solar PV system were studied. The dust deposition rates are significantly different for different dust sizes. The profiles of dust deposition rates are similar for different wind velocities. The deposition mechanisms of different size dust on solar PV panel were analyzed. An empirical model was adopted for predicting the PV efficiency reduction.